2008
DOI: 10.1111/j.1365-2702.2007.02090.x
|View full text |Cite
|
Sign up to set email alerts
|

From critical care to comfort care: the sustaining value of humour

Abstract: Humour is often considered trivial or unprofessional; this research verifies that it is neither. The value of humour resides, not in its capacity to alter physical reality, but in its capacity for affective or psychological change which enhances the humanity of an experience, for both care providers and recipients of care. Relevance to clinical practice. In the present era which emphasises technology, efficiency and outcomes, humour is crucial for promoting team relationships and for maintaining the human dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 29 publications
4
62
0
9
Order By: Relevance
“…Patently, there will be times when humor is not appropriate [30]. However, according to most studies [3133] humor in care is something valuable which fosters a relationship, eases tension and more. Using physical contact and humor when caring for a patient requires great mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Patently, there will be times when humor is not appropriate [30]. However, according to most studies [3133] humor in care is something valuable which fosters a relationship, eases tension and more. Using physical contact and humor when caring for a patient requires great mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…For Jean, humour use may ‘simply’ humanise the interaction (Dean & Major 2008). However, Heather and Kay’s harsh humour initiation about potential areas of discord may also indicate to Jean their (i) awareness of pertinent issues, e.g.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…From nearly 300 hours of observations, the researchers found that humour served to “enable co-operation, relieve tensions, develop emotional flexibility, and to ‘humanise’ the healthcare experience.”10 The two studies also included conversations with patients as well as health professionals, regarding how they felt about humour in medical settings. The authors conclude: “The value of humour resides not in its capacity to alter physical reality, but in its capacity for affective or psychological changes which enhances the humanity of the experience, for both care providers and the recipients of care.”…”
Section: The Value Of Humourmentioning
confidence: 99%